2018
DOI: 10.1007/s11481-018-9783-8
|View full text |Cite
|
Sign up to set email alerts
|

A Role for the Non-Receptor Tyrosine Kinase Abl2/Arg in Experimental Neuroinflammation

Abstract: Multiple sclerosis is a neuroinflammatory degenerative disease, caused by activated immune cells infiltrating the CNS. The disease etiology involves both genetic and environmental factors. The mouse genetic locus, Eae27, linked to disease development in the experimental autoimmune encephalomyelitis (EAE) model for multiple sclerosis, was studied in order to identify contributing disease susceptibility factors and potential drug targets for multiple sclerosis. Studies of an Eae27 congenic mouse strain, revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…ABL2 plays an important role in the proliferation and invasion of cancer cells 36 and although a potential role of ABL2 has been reported in immune disorders such as multiple sclerosis and diabetes, the exact role of ABL2 in these diseases is not yet clear. 49,50 The findings presented here suggest that the rs3829794 CC genotype, which protects against acquiring VKH, might be due to a decreased expression of ABL2. Recent studies have shown that inhibition of ABL kinases ameliorates experimental autoimmune encephalomyelitis, an animal model for multiple sclerosis, 49 which is further supported by our hypothesis.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…ABL2 plays an important role in the proliferation and invasion of cancer cells 36 and although a potential role of ABL2 has been reported in immune disorders such as multiple sclerosis and diabetes, the exact role of ABL2 in these diseases is not yet clear. 49,50 The findings presented here suggest that the rs3829794 CC genotype, which protects against acquiring VKH, might be due to a decreased expression of ABL2. Recent studies have shown that inhibition of ABL kinases ameliorates experimental autoimmune encephalomyelitis, an animal model for multiple sclerosis, 49 which is further supported by our hypothesis.…”
Section: Discussionmentioning
confidence: 70%
“…49,50 The findings presented here suggest that the rs3829794 CC genotype, which protects against acquiring VKH, might be due to a decreased expression of ABL2. Recent studies have shown that inhibition of ABL kinases ameliorates experimental autoimmune encephalomyelitis, an animal model for multiple sclerosis, 49 which is further supported by our hypothesis. This SNP also had an effect on the proliferation of PBMCs and the production of anti-inflammatory cytokines that are potentially involved in the pathogenesis of VKH.…”
Section: Discussionmentioning
confidence: 70%
“…For example, the products of the four most enriched candidate genes, AQP1, ABL2, CHD3, and RELN, participate in inflammatory activation, cell adhesion and migration, wound healing, and organ regeneration [36][37][38][39][40][41]. In addition, they play important roles in the nervous system and are associated with central and periphery neuropathies [39,[42][43][44][45][46]. Motor proteins, which are the products of another subset of enriched genes, are essential for axonal transportation and function at immunological synapses [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…However, Ras signaling pathway containing ABL2 downregulated by the hsa‐miR‐15 family (miR‐15a‐5p, miR‐15b‐5p, and miR‐16‐5p) might be involved and hence warrants further investigation. ABL2 encodes the non‐receptor tyrosine kinase ARG; the ARG C‐terminus is a key regulator of actin cytoskeleton rearrangement, 62 which is involved in the stability and morphogenesis of the dendritic spine 63,64 . Hence, ABL2/ARG non‐receptor tyrosine kinase deficiency destabilizes the dendritic arbor and reduces its density by damaging the dendritic spine 27 .…”
Section: Discussionmentioning
confidence: 99%